Pitch Blade Control Prototype Design for Vertical Axis Wind Power Plant - Antonius Rajagukguk; Winggi Arafanaldy; Anhar Anhar; Nurhalim Nurhalim (Universitas Ahmad Dahlan, 2022)
One alternative energy that is easy and can be used is wind. This energy is utilized through wind turbines which have two general types, namely horizontal and vertical axis wind turbines. This wind turbine can move by utilizing the energy available in the wind to rotate the turbine. The problem with wind turbines is self-starting is difficult to achieve. This can be caused by several factors, such as slow wind speed and erratic wind direction. In addition, wind turbines also have low-efficiency values. Therefore, our contribution to this research is to design a blade controller on a vertical axis wind turbine. This blade control is designed by utilizing the pitch angle by using actuators that are applied to each blade based on the Proportional, Integral & Derivative (PID) algorithm. The PID algorithm is used to find the appropriate pitch angle value on a vertical axis wind turbine. The effect of the pitch angle on the wind turbine serves to maintain the mechanical power value by the available power in the wind. This research was conducted using a simulation method (MATLAB). In this study, it was found that this wind energy conversion simulation produces maximum mechanical power when the wind speed varies is 1723 Watt and when the wind speed is 7 m/s, mechanical power achieved is 362.595 Watt.